Synthesis of Nanostructured Anatase Mesoporous Membranes with Photocatalytic and Separation Capabilities for Water Ultrafiltration Process - Vahideh Tajer-Kajinebaf; Hossein Sarpoolaky; Toraj Mohammadi (International Journal of Photoenergy)
In this work, the nanostructured anatase mesoporous membranes were prepared for water ultrafiltration (UF) process with photocatalytic and physical separation capabilities. A macroporous substrate was synthesized from α-Al2O3, then a colloidal titania sol was used for the preparation of the intermediate layer. Also, the membrane top layer was synthesized by deposition and calcination of titania polymeric sol on the intermediate layer. The characterization was performed by DLS, TG-DTA, XRD, BET, FESEM, TEM, and AFM techniques. Also, the filtration experiments were carried out based on separation of methyl orange from aqueous solution by a membrane setup with a dead-end filtration cell. Photocatalytic activity of the membranes was evaluated by methyl orange photodegradation using UV-visible spectrophotometer. The mean particle size of the colloidal and polymeric sols was 14 and 1.5 nm, respectively. The anatase membranes exhibited homogeneity, with the surface area of 32.8 m2/g, the mean pore size of 8.17 nm, and the crystallite size of 9.6 nm. The methyl orange removal efficiency by the mesoporous membrane based on physical separation was determined to be 52% that was improved up to 83% by a coupling photocatalytic technique. Thus, the UF membrane showed a high potential due to its multifunctional capability for water purification applications.